Health Related Quality of Life and Residual Symptoms in Prostatic Surgical Treatment at Bethesda Hospital Yogyakarta: a Retrospective Study - Daniel Mahendra Krisna; Hariatmoko Hariatmoko; Rizaldy Taslim Pinzon (Althea Medical Journal, 2017)
Background: The incidence of Prostate Enlargement (PE) has been increasing over the years. The satisfaction towards the treatment result and life quality (QOL) improvement must be the key point of PE treatment. QOL is affected by many conditions, such as age, socioeconomic status, comorbid disease, and type of surgery. The objective of the study was to assess the QOL in PE patients post surgery, to explore the predictor factor, and to assess the satisfaction related to urinary functionality in the Indonesian context. Methods: A retrospective study was conducted and the subjects were all PE patients who underwent surgical treatment. EQ-5D-5L/EQ-VAS and Index Quality of Life (IQL) were used to assess the patient’s QOL & treatment satisfaction. The subjects were divided into several sub-groups based on age, type of surgery, comorbid condition, type of ward, funding source, histopathological result, and the year of treatment. The collected data wee analyzed using Mann-Whitney test, Kruskal Wallis test, or Chi-square test, Spearman’s rho test and multiple linear regression. Results: All the 149 subjects were at the average age of 69.09 years . There were no significant statistical differences in QOL between age, comorbid conditions, and histopathology result. Health insurance (HI) was significantly associated with QOL. There were improvements of IQL subjects. The most symptoms remaining was frequency (47.4%).Conclusions: Life improvement must be the major purpose of PE therapy. The association between HI with QOL suggests that a better HI in developing countries can ensure a better quality of life outcome.